Daur Ulang Kombinasi Limbah Pertanian menjadi Kompos Berkualitas - Moh Waisul Karomi; Mis war; Sugeng Winarso (Pascasarjana Universitas Jember, 2021)
Waste Population in Indonesia According to the Ministry of Environment and Forestry (2015), the amount of landfill has reached 175,000 tonnes/day or the equivalent of 64 million tonnes/year. Utilization of the waste is used as solid organic fertilizer which can be applied to soil to increase crop production. The research used waste from cocopeat, banana fronds and maggot pupae. This study aims to determine the characteristics of solid organic fertilizers made from cocopeat waste, banana fronds and maggot pupae. In addition, there are materials, namely EM4 as microorganisms, molasses as a food source for microorganisms and water to regulate humidity during the composting process. Each parameter will be tested and compared with the minimum technical requirements for solid organic fertilizer contained in Permentan/SR.140/10/2011. The results showed that solid organic fertilizers made from cocopeat, banana fronds and maggot pupae were of the same quality as the minimum technical requirements, namely solid organic fertilizer. includes parameters C/N ratio, pH, water content and (N+P205+K20). The results of the best treatment research on sample A (100 ml/ EM4) meet the standards because above 4% the content of the nitrogen presentation is 4.72%, phospor (P205) is 4.40% while the potassium content is below the standard for making solid organic fertilizer with a percentage of 3.96% for the variation of 100 ml/EM4, 23.51% C-Organic has met the minimum standard, namely 15-25% and C/N ratio of 4.98% is below the standard, which is below 5%. Keywords : Banana fronds, Cocopeat, EM4, Maggot pupae, Waste quality